KOMPARASI REAKTIFITAS PELARUT DARI MINYAK BAKAR DAN RESIDU RANTAI PANJANG PADA PENCAIRAN BATUBARA BANKO - Hidayat, Herman; Nataadmadja, Nasikin (Jurnal Energi dan Lingkungan (Enerlink), 2007)
The needs of fuel, especially for automotive fuel, in Indonesia keeps onincreasing, while petroleum reserves is getting lessen everyday. One alternativeto achieve the diversified energy strategy for the transportation sector is theutilization of the Indonesian low rank coal reserves through the implementation ofcoal liquefaction technology. Coal liquefaction process that has been done beforewas found economically and technically less effective. Those are the reasons fordoing coal liquefaction research using petroleum residue as the solvent, namelyco-processing, which expected to give a better performance than the standardcoal liquefaction. The feedstocks are lignite coal from Central Banko, petroleumresidue (fuel oil and long residue), limonite catalyst from Soroako and hydrogengas. The reactions were carried out in a stirred batch autoclave reactor at 120Kg/cm2 of initial hydrogen pressure and 450oC for 1 hour, at 2 of S/Fe atomicratio and 2 of solvent/coal weight ratio. The liquid products were fractionated byvacuum distillation and the gaseous products were analyzed by gaschromatography. It showed that co-processing with long residue as the solvent isbetter than fuel oil or standard coal liquefaction, with 39.17 wt% daff of oil yiled.The cetane index of middle oil fraction was 27.8 and the efficiency of hydrogenconsumption was 23.68 (oil yield/hydrogen consumption).Kata kunci: pencairan batubara, co-processing, residu minyak bumi, batubaralignit